2023
DOI: 10.1007/s10265-023-01446-8
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated analysis of metabolome and transcriptome reveals key candidate genes involved in flavonoid biosynthesis in Pinellia ternata under heat stress

Abstract: Pinellia ternata (Thunb.) Breit. is an important traditional Chinese medicinal herb and very sensitive to high temperatures. To gain a better understanding of flavonoid biosynthesis under heat stress in P. ternata, we performed integrated analyses of metabolome and transcriptome data. P. ternata plants were subjected to a temperature of 38 °C, and samples were collected after 10 d of treatment. A total of 502 differential accumulated metabolites and 5040 different expressed transcripts were identified, with fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…We further noticed that the four flavonoids and four saccharides reached their peak contents in ZD under heat stress. Similar to our results, related transcriptome analyses have shown that saccharides metabolites and flavonoids play the crucial role in response to heat stress [47][48][49].…”
Section: Discussionsupporting
confidence: 91%
“…We further noticed that the four flavonoids and four saccharides reached their peak contents in ZD under heat stress. Similar to our results, related transcriptome analyses have shown that saccharides metabolites and flavonoids play the crucial role in response to heat stress [47][48][49].…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of DEGs in different species of the same genus has been involved in many species studies (Guo et al, 2021 ; Jiang et al, 2021 ; Zhu, 2020 ). Studies had shown that high expression of SVP resulted in smaller flowers and also inhibited the flowering process in most dicotyledonous plants (Jaudal et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that three types responses have been documented in plants under HTS. HTS may alter metabolite event and inhibit various physiological and biochemical reactions of plants, including changing in water status, cell membrance stability, photosynthesis, secondary metabolites, plant hormone levels [11]. HTS can rapidly inhibit photosynthesis by changing the internal structure of the chloroplasts, reducing the abundance of photosynthetic pigments, and damaging photosystem II [12].…”
Section: Introductionmentioning
confidence: 99%